Nano water suspending agent of oxine-copper and preparation method of nano water suspending agent
By preparing quinoline copper nanowater suspension agent with particle size distribution between 200 and 900 nm, the problem of excessive particle size of the existing quinoline copper water suspension agent is solved, the efficacy and utilization rate are improved, and the risks of pesticide residues and environmental pollution are reduced.
Patent Information
- Application Number
- CN202411805328.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-18
AI Technical Summary
The particle size of existing quinoline copper water suspension agents is generally within 5 microns, resulting in low efficiency of invasion of active ingredients and attacking targets, affecting the efficacy of the drug, and multiple applications lead to excessive pesticide residues, causing environmental pollution and food safety risks.
Nanowater suspension agents with quinoline copper are used, and their particle sizes are distributed between 200 and 900 nm. By reasonably combining dispersants, co-dispersants, wetting agents and thickening agents, excellent dispersibility and stability are formed, and the efficacy and utilization of pesticide active ingredients are improved.
It improves the efficacy and utilization rate of pesticide active ingredients, reduces the amount and number of use of the agent, reduces the risks of pesticide residues and environmental pollution, and improves food safety and the safety of new pesticide preparations to the ecological environment.
Smart Images

Figure BDA0005179060800000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of pesticides, and particularly relates to a nanometer aqueous suspension of quinoline copper and a preparation method thereof. Background Art
[0002] Aqueous suspension concentrates, also known as colloidal suspension concentrates, refer to a relatively stable dispersion system formed by dispersing water-insoluble or poorly soluble original drugs into water under the action of additives (dispersants, wetting agents, thickeners, antifreeze agents, pH adjusters, preservatives and defoamers, etc.). The particle size range of existing aqueous suspension concentrates is usually controlled at around 5 microns, that is, D90≤5 microns. It belongs to a thermodynamically unstable polydisperse system and can be evenly mixed and dispersed with water in any proportion. It is easy to process and use. This dosage form is based on water and almost no organic solvents are added, so it has the advantages of safety, environmental protection and convenience.
[0003] However, there are also many shortcomings, which are reflected in the process of preparation processing and product sales. Water suspension concentrates generally have the following problems: ⑴ Dispersion problem, the mutual attraction between particles leads to flocculation and aggregation between the original drug particles, which directly affects the shelf life of the product; ⑵ Ostwald ripening problem, Ostwald ripening causes changes in the particle size distribution of pesticide particles during storage, and the growth of particle size directly affects the efficacy of the drug; ⑶ Suspension stability problem, which leads to stratification and particle sedimentation of the suspension system under the action of the gravity field. Among them, the reason for the Ostwald ripening problem is that the size of pesticide particles is related to the solubility between the various crystalline states of the pesticide active ingredients. Therefore, if you want to reduce the Ostwald ripening effect, you must reduce the product particle size and distribution range.
[0004] At the same time, the specific measures currently available to improve the stability of water suspension concentrates include: ⑴ Selecting solid pesticides with low water solubility and stable crystals to be processed into water suspension concentrates; ⑵ Controlling the particle size and distribution of the pesticide particles after grinding, the particle size is generally controlled within 5 microns, and the particle size distribution is as narrow as possible; ⑶ Reasonably controlling the viscosity of the water suspension concentrate, and selecting appropriate suspending agents without affecting the dispersibility, fluidity and other indicators of the water suspension concentrate.
[0005] However, the particle size of existing quinoline copper aqueous suspension is generally within 5 microns, that is, D90≤5 microns. The particle size is still relatively large, which is not conducive to the active ingredients to invade and attack the target. The biological activity and target utilization rate are low, which affects the efficacy of the drug. Especially when crop diseases break out, multiple applications of pesticides are required, resulting in excessive pesticide residues in crops, which in turn causes environmental pollution and food safety risks. Summary of the invention
[0006] In view of the problems raised by the above background technology, the purpose of the present invention is to provide a nanometer aqueous suspension of quinoline copper and a preparation method thereof.
[0007] In order to achieve the above technical objectives, the technical solution adopted by the present invention is as follows:
[0008] A nanometer water suspension of quinoline copper comprises the following components by mass percentage: 20-45% of quinoline copper, 5-20% of dispersant, 1-5% of dispersant aid, 1-5% of wetting agent, 0.1-1% of preservative, 0.1-1% of defoamer, 1-10% of antifreeze agent, 0.2-3% of thickener, and the balance is water.
[0009] It is further defined that the mass percentage composition of the raw materials is as follows: quinoline copper 20-45%, dispersant 7-15%, dispersant aid 2-4%, wetting agent 1-2%, preservative 0.1-0.3%, defoaming agent 0.1-0.3%, antifreeze 1-6%, thickener 0.2-3%, and the balance is water.
[0010] It is further defined that the dispersant is one of a polycarboxylate dispersant, a phosphate dispersant and a polyether sulfate dispersant, and the dispersant may also be a mixed dispersant of a polycarboxylate and a polyether sulfate, or a mixed dispersant of a phosphate and a polyether sulfate.
[0011] It is further defined that the dispersant is an EO-PO block polyether copolymer dispersant.
[0012] It is further specified that the wetting agent is a fatty alcohol polyoxyethylene ether or diisopropylnaphthalene sulfonate wetting agent.
[0013] It is further defined that the preservative is a benzisothiazolinone preservative, and the benzisothiazolinone preservative should be formulated into a 2% to 3% aqueous solution when used.
[0014] It is further defined that the defoaming agent is one of modified polyether, acetylene glycol, and silicone defoaming agent, and the antifreeze agent is one of propylene glycol, ethylene glycol, and urea.
[0015] It is further defined that the thickener is one or more of xanthan gum, magnesium aluminum silicate, cellulose and hydroxyethyl cellulose, and the xanthan gum needs to be prepared into an aqueous solution when used, and the xanthan gum needs to be prepared into a 1-2% aqueous solution when used.
[0016] A method for preparing a nanometer aqueous suspension of quinoline copper, characterized in that it comprises the following steps:
[0017] S1: Mix and stir evenly 20-45% of quinoline copper, 5-20% of dispersant, 1-5% of dispersant aid, 1-5% of wetting agent, more than 90% of thickener (0.2-3%), 1-10% of antifreeze, 40-60% of defoamer (0.1-1%), and 60-80% of water;
[0018] S2: adding the mixture in S1 into a nano-scale sand mill with zirconium oxide beads for sand grinding;
[0019] S3: After the particle size of S2 is sand-milled to 200-900 nm, add the remaining 40-60% defoamer, the remaining thickener, the preservative and the remaining water, stir and disperse evenly to obtain the nano pesticide suspension.
[0020] It is further defined that in S1, 0.9-2% of magnesium aluminum silicate thickener is added in the mixing and stirring step, in S2, the particle size of zirconium oxide beads is 0.1-0.6 mm, and in S3, 0.1-0.5% of xanthan gum aqueous solution thickener is added after the particle size reaches 200-900 nm.
[0021] The beneficial effects of the present invention are:
[0022] 1. The particle size distribution of the nano pesticide water suspension prepared by the present invention is between 200 and 900 nm, which helps the active ingredients of the original medicine to penetrate through the tissue membrane of plant tissue or bacteria, and promotes the bactericidal effect of the active ingredients of the original medicine on the target; through the reasonable combination and balance of dispersants, co-dispersants and wetting agents, excellent dispersibility is formed, which can effectively avoid the aggregation and particle size growth of particles in the nano suspension, has good quality stability, and has excellent wetting properties. By reducing the surface tension on the target, the hydrophilicity or lipophilicity of the nanoparticles is increased, and the adhesion and deposition amount on the target are increased, thereby improving the efficacy and utilization rate of the active ingredients of the pesticide, reducing the amount and frequency of use of the agent, and reducing agricultural residues and pollution to the environment.
[0023] 2. The present invention can significantly improve the surface tension and stability between various constituent phases in the water suspension by optimizing the combination of various dispersants, dispersants, wetting agents and a small amount of thickeners, forming a uniform and stable dispersion system, promoting the penetration and absorption of effective ingredients at the target position, improving the adhesion, deposition and distribution performance of pesticide active ingredients on the leaf surface or bacterial surface, increasing the effective utilization rate of pesticides by more than 20%, and reducing the loss of pesticides on the surface of plants and leaves, improving the way and efficiency of pesticide active ingredients exerting biological activity on the target, directly penetrating the plant and achieving internal transmission, or directly penetrating the wax layer of the insect body, and significantly improving the bactericidal effect.
[0024] 3. The preparation method of the present invention realizes the preparation of nano-pesticide aqueous suspension without significantly increasing the cost, improves the efficacy, and accelerates the degradation process of pesticide residues in plants, water bodies and other environments, improves the safety of nano-pesticide aqueous suspension to organisms and the environment, improves the safety of food, reduces the risk of agricultural product residues and environmental pollution, and enhances the safety of new pesticide preparations to the ecological environment. DETAILED DESCRIPTION
[0025] In order to enable those skilled in the art to better understand the present invention, the technical solution of the present invention is further described below in conjunction with embodiments.
[0026] The invention discloses a nanometer aqueous suspension of quinoline copper, which comprises the following components by mass percentage: 20-45% of quinoline copper, 5-20% of dispersant, 1-5% of dispersant aid, 1-5% of wetting agent, 0.1-1% of preservative, 0.1-1% of defoamer, 1-10% of antifreeze agent, 0.2-3% of thickener, and the balance is water.
[0027] Preferably, the raw materials are composed of the following in mass percentage: 20-45% quinoline copper, 7-15% dispersant, 2-4% dispersant, 1-2% wetting agent, 0.1-0.3% preservative, 0.1-0.3% defoamer, 1-6% antifreeze, 0.2-3% thickener, and the balance is water.
[0028] In some embodiments, the mass percentage of quinoline copper in the nano water suspension is 33.5-40%.
[0029] In some other more preferred embodiments, the mass percentage of quinoline copper in the nano water suspension is 33.5% or 40%.
[0030] Preferably, the dispersant is one of a polycarboxylate dispersant, a phosphate dispersant and a polyether sulfate dispersant. The dispersant may also be a mixed dispersant of a polycarboxylate and a polyether sulfate, or a mixed dispersant of a phosphate and a polyether sulfate.
[0031] In some embodiments, the mass percentage of the dispersant in the nano aqueous suspension is 6-15%.
[0032] In some embodiments, the dispersant is a polycarboxylate dispersant selected from the group consisting of Shanghai Perun Technology PRTech-D8868, Huntsman TERSPPPPERSE 2500, and Croda Atlox 4913.
[0033] In some embodiments, the dispersant is a phosphate ester dispersant selected from the group consisting of Shanghai Perun Technology PRTech-D8601, Huntsman TERSPPPPERSE 2210, Solvay SOPROPHOR SC, and Clariant Dispersogen LFS.
[0034] In some embodiments, the dispersant is a polyether sulfate dispersant such as Shanghai Pairun Technology PRTech-D8602 and Solvay SOPROPHOR FD.
[0035] In some embodiments, the dispersant is a mixed dispersant of polycarboxylate and polyether sulfate, such as PRTech-D1807 from Shanghai Perun Technology or a mixture of Huntsman TERSPPPPERSE 2500 and Solvay SOPROPHOR FD;
[0036] In some embodiments, the dispersant is a mixed dispersant of phosphate ester and polyether sulfate, such as PRTech-D1806 from Shanghai Pairun Technology or one of Clariant Dispersogen LFS and Solvay SOPROPHOR FD.
[0037] Preferably, the dispersant is an EO-PO block polyether copolymer dispersant.
[0038] In some embodiments, the mass percentage of the dispersant in the nano water suspension is 1-5%.
[0039] In some embodiments, the dispersant is one of the EO-PO block polyether copolymer dispersants such as Shanghai Pairun Technology PRTech-D8969 or Croda Atlox G-5002L.
[0040] Preferably, the wetting agent is a fatty alcohol polyoxyethylene ether or diisopropylnaphthalene sulfonate wetting agent.
[0041] In some embodiments, the wetting agent is fatty alcohol polyoxyethylene ether, such as Shanghai Pairun Technology PRTech-W6600 or Dow TERGITOL W-600.
[0042] In some embodiments, the wetting agent is diisopropylnaphthalene sulfonate, such as Shanghai Pairun Technology PRTech-W6670, Aksu Morwet IP, or Italy Puset 704.
[0043] In some embodiments, the mass percentage of the wetting agent in the nano water suspension is 0.5-1%;
[0044] In some embodiments, the mass percentage of the wetting agent in the nano aqueous suspension is 1%.
[0045] Preferably, the preservative is a benzisothiazolinone preservative, which should be formulated into a 2% to 3% aqueous solution when used.
[0046] In some embodiments, the mass percentage of the preservative in the nano aqueous suspension is 0.1 to 1%;
[0047] In some embodiments, the mass percentage of the wetting agent in the nano water suspension is 0.1 to 0.3%;
[0048] In some embodiments, the mass percentage of the wetting agent in the nano aqueous suspension is 0.2%.
[0049] Preferably, the defoaming agent is one of modified polyether, acetylene glycol, and silicone defoaming agent, and the antifreeze agent is one of propylene glycol, ethylene glycol, and urea.
[0050] In some embodiments, the mass percentage of the defoaming agent in the nano water suspension is 0.1 to 1%;
[0051] In some embodiments, the mass percentage of the defoaming agent in the nano water suspension is 0.1 to 0.3%;
[0052] In some embodiments, the mass percentage of the defoaming agent in the nano aqueous suspension is 0.2%.
[0053] In some embodiments, the defoaming agent is a modified polyether defoaming agent (Shanghai Pairun Technology PRTech-DE80).
[0054] In some embodiments, the mass percentage of the antifreeze agent in the nano water suspension is 1 to 10%;
[0055] In some embodiments, the mass percentage of antifreeze in the nano water suspension is 3-6%;
[0056] In some embodiments, the mass percentage of the antifreeze agent in the nano water suspension is: propylene glycol: 4%.
[0057] Preferably, the thickener is one or more of xanthan gum, magnesium aluminum silicate, cellulose and hydroxyethyl cellulose. The xanthan gum needs to be prepared into an aqueous solution when used. The xanthan gum needs to be prepared into a 1-2% aqueous solution when used.
[0058] In some embodiments, the mass percentage of the thickener in the nano water suspension is 0.2-3%;
[0059] In some embodiments, the mass percentage of the thickener in the nano water suspension is 0.2 to 2%;
[0060] In some embodiments, the mass percentage of the thickener in the nano water suspension is 2% of xanthan gum aqueous solution and magnesium aluminum silicate.
[0061] A method for preparing a nanometer aqueous suspension of quinoline copper, characterized in that it comprises the following steps:
[0062] S1: Mix and stir evenly 20-45% of quinoline copper, 5-20% of dispersant, 1-5% of dispersant aid, 1-5% of wetting agent, more than 90% of thickener (0.2-3%), 1-10% of antifreeze, 40-60% of defoamer (0.1-1%), and 60-80% of water;
[0063] S2: adding the mixture in S1 into a nano-scale sand mill with zirconium oxide beads for sand grinding;
[0064] S3: After the particle size of S2 is sand-milled to 200-900 nm, add the remaining 40-60% defoamer, the remaining thickener, the preservative and the remaining water, stir and disperse evenly to obtain the nano pesticide suspension.
[0065] Preferably, in S1, 0.9-2% of magnesium aluminum silicate thickener is added in the mixing and stirring step, in S2, the particle size of the zirconium oxide beads is 0.1-0.6 mm, and in S3, 0.1-0.5% of xanthan gum aqueous solution thickener is added after the particle size reaches 200-900 nm.
[0066] Example 1
[0067] A 33.5% quinoline copper nanoparticle water suspension, the composition of which is shown in Table 1:
[0068] Table 1
[0069] Components composition% Remark 98% Quinoline Copper 33.5 (100% discount) Active ingredients PRTech-D1806 7 Dispersants PRTech-D8969 2 Dispersant PRTech-W6670 0.5 Wetting Agents Propylene glycol 4 antifreeze Magnesium aluminum silicate 1.4 Thickener 2% xanthan gum aqueous solution 7 Thickener BIT 0.2 preservative PRTech-DE80 0.1 Defoaming agent water Make up 100 Carrier
[0070] The preparation method of the quinoline copper nano-scale suspension comprises:
[0071] 33.5% quinoline copper, 7% dispersant PRTech-D1806, 2% co-dispersant PRTech-D8969, 0.5% wetting agent PRTech-W6670, 4% propylene glycol, 1.4% magnesium aluminum silicate, 0.2% preservative BIT, 0.1% defoamer PRTech-DE80 (40%) was mixed with 80% of the total amount of water, stirred for 5 minutes, added to a nano sand mill (pre-installed with 750g of 0.3mm zirconium oxide beads) for sand milling, and after sand milling for 1 hour, the sand milling was stopped after the particle size was detected to be 200nm, and the remaining 0.1% defoamer PRTech-DE80 and 7% 2% xanthan gum aqueous solution suspending agent were used, and the remaining water was added, stirred evenly, and a homogeneous dispersion system was formed to obtain a 33.5% quinoline copper nano water suspension with a particle size of 200nm.
[0072] It should be noted that the first addition of 1.4% aluminum magnesium silicate plus the second addition of 7% 2% xanthan gum aqueous solution suspending agent, by weight, has a thickener content (by weight): 1.4% + 7% x 2% = 1.54%.
[0073] Example 2
[0074] A 33.5% quinoline copper nanoparticle water suspension, the composition of which is shown in Table 2:
[0075] Table 2
[0076] Components composition% Remark 98% Quinoline Copper 33.5 (100% discount) Active ingredients PRTech-D1807 7 Dispersants PRTech-D8969 2 Dispersant PRTech-W6600 1 Wetting Agents Propylene glycol 4 antifreeze Magnesium aluminum silicate 1.4 Thickener 2% xanthan gum aqueous solution 7 Thickener BIT 0.2 preservative PRTech-DE80 0.1 Defoaming agent water Make up 100 Carrier
[0077] The preparation method of the quinoline copper nano-scale suspension comprises:
[0078] 33.5% quinoline copper, 7% dispersant PRTech-D1807, 2% co-dispersant PRTech-D8969, 1% wetting agent PRTech-W6600, 4% propylene glycol, 1.4% magnesium aluminum silicate, 0.2% preservative BIT, 0.1% defoamer PRTech-DE80 (40%) was mixed with 80% of the total amount of water, stirred for 5 minutes, added to a nano sand mill (pre-installed with 750g of 0.3mm zirconium oxide beads) for sand milling, and after sand milling for 1 hour, the sand milling was stopped after the particle size was detected to be 200nm, and the remaining 0.1% defoamer PRTech-DE80 and 7% 2% xanthan gum aqueous solution suspending agent were used, and the remaining water was added, stirred evenly, and a homogeneous dispersion system was formed to obtain a 33.5% quinoline copper nano water suspension with a particle size of 200nm.
[0079] It should be noted that the first addition of 1.4% aluminum magnesium silicate plus the second addition of 7% 2% xanthan gum aqueous solution suspending agent, by weight, has a thickener content (by weight): 1.4% + 7% x 2% = 1.54%.
[0080] Example 3
[0081] A 40% quinoline copper nanoparticle water suspension, the composition is shown in Table 3:
[0082] Table 3
[0083] Components composition% Remark 98% Quinoline Copper 40(100% off) Active ingredients PRTech-D1806 9 Dispersants PRTech-D8969 2 Dispersant PRTech-W6670 1 Wetting Agents Propylene glycol 4 antifreeze Magnesium Aluminum Silicate 1.2 Thickener 2% xanthan gum aqueous solution 6 Thickener BIT 0.2 preservative PRTech-DE80 0.1 Defoaming agent water Make up 100 Carrier
[0084] The preparation method of the quinoline copper nano-scale suspension comprises:
[0085] 50% of the total amount of 40% quinoline copper, 9% dispersant PRTech-D1806, 2% co-dispersant PRTech-D8969, 1% wetting agent PRTech-W6670, 4% propylene glycol, 1.2% magnesium aluminum silicate, 0.2% preservative BIT, and 0.1% defoamer PRTech-DE80 were mixed with 80% of the total amount of water, stirred for 5 minutes, added to a nano sand mill (pre-installed with 750g of 0.3mm zirconia beads) and sanded. After sanding for 1 hour, the sanding was stopped after the particle size was detected to be 200nm, and the remaining 0.1% defoamer PRTech-DE80 and 6% 2% xanthan gum aqueous solution suspending agent were used, and the remaining water was added, stirred evenly, and a homogeneous dispersion system was formed to obtain a 40% quinoline copper nano water suspension with a particle size of 200nm.
[0086] It should be noted that the first addition of 1.2% magnesium aluminum silicate plus the second addition of 6% 2% xanthan gum aqueous solution suspending agent, by weight, has a thickener content (by weight): 1.2% + 6% x 2% = 1.32%.
[0087] Example 4
[0088] A 40% quinoline copper nanoparticle water suspension, the composition is shown in Table 4:
[0089] Table 4
[0090] Components composition% Remark 98% Quinoline Copper 40(100% off) Active ingredients PRTech-D1807 9 Dispersants PRTech-D8969 2 Dispersant PRTech-W6600 1 Wetting Agents Propylene glycol 4 antifreeze Magnesium aluminum silicate 1.2 Thickener 2% xanthan gum aqueous solution 6 Thickener BIT 0.2 preservative PRTech-DE80 0.1 Defoaming agent water Make up 100 Carrier
[0091] The preparation method of the quinoline copper nano-scale suspension comprises:
[0092] 50% of the total amount of 40% quinoline copper, 9% dispersant PRTech-D1807, 2% co-dispersant PRTech-D8969, 1% wetting agent PRTech-W6600, 4% propylene glycol, 1.2% magnesium aluminum silicate, 0.2% preservative BIT, and 0.1% defoamer PRTech-DE80 were mixed with 80% of the total amount of water, stirred for 5 minutes, added to a nano sand mill (pre-installed with 750g of 0.3mm zirconia beads) and sanded. After sanding for 1 hour, the sanding was stopped after the particle size was detected to be 200nm, and the remaining 0.1% defoamer PRTech-DE80 and 6% 2% xanthan gum aqueous solution suspending agent were used, and the remaining water was added, stirred evenly, and a homogeneous dispersion system was formed to obtain a 40% quinoline copper nano water suspension with a particle size of 200nm.
[0093] It should be noted that the first addition of 1.2% magnesium aluminum silicate plus the second addition of 6% 2% xanthan gum aqueous solution suspending agent, by weight, has a thickener content (by weight): 1.2% + 6% x 2% = 1.32%.
[0094] Test example: Detection of nanosuspension containing copper quinoline.
[0095] The initial particle size, normal storage particle size, and hot storage particle size of the nanosuspension containing copper quinoline in Examples 1-4 were tested respectively, and the results are shown in Table 5. The initial particle size, normal storage particle size, and hot storage particle size were all analyzed and measured using a Malverm 3000 nanometer detector to measure the D98 value; the normal storage particle size was measured after being placed at room temperature for 14 days; the hot storage particle size was measured after being placed in a DHP-9162 electric constant temperature incubator at 54°C for 14 days and then taken out and cooled to room temperature.
[0096] Table 5. Detection results of nanosuspension particle size in different embodiments
[0097] Table 5
[0098]
[0099] As can be seen from Table 5, the nanosuspensions of Examples 1-4 of the present invention have good particle size stability. Compared with the initial particle size, the normal storage particle size and the hot storage particle size only increase slightly, both less than 0.9 μm, which are within a controllable range.
[0100] In addition, the nanosuspension concentrates of Examples 1-4 were placed at room temperature for 14 days and stored at 54° C. for 14 days, respectively, and the suspension rates were tested with reference to Method 1 in GB / T14825-2006 Method for Determining Suspension Rate of Pesticides. The suspension rates of the nanosuspension concentrates of each example were all higher than 98%, meeting the relevant requirements for suspension concentrates.
[0101] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the technology may modify or change the above embodiments without violating the spirit and scope of the present invention. Therefore, all equivalent modifications or changes made by those with ordinary knowledge in the technical field without departing from the spirit and technical ideas disclosed by the present invention should still be covered by the claims of the present invention.
Claims
1. A nanometer aqueous suspension of quinoline copper, characterized in that: The invention comprises the following components by mass percentage: 20-45% of quinoline copper, 5-20% of dispersant, 1-5% of dispersant aid, 1-5% of wetting agent, 0.1-1% of preservative, 0.1-1% of defoaming agent, 1-10% of antifreeze agent, 0.2-3% of thickener and the balance is water.
2. The nanometer aqueous suspension of quinoline copper according to claim 1, characterized in that: The raw materials are composed of 20-45% quinoline copper, 7-15% dispersant, 2-4% dispersant, 1-2% wetting agent, 0.1-0.3% preservative, 0.1-0.3% defoamer, 1-6% antifreeze, 0.2-3% thickener and the balance is water.
3. A nanometer aqueous suspension of quinoline copper according to claim 2, characterized in that: The dispersant is one of a polycarboxylate dispersant, a phosphate dispersant and a polyether sulfate dispersant. The dispersant may also be a mixed dispersant of a polycarboxylate and a polyether sulfate, or a mixed dispersant of a phosphate and a polyether sulfate.
4. A nanometer aqueous suspension of quinoline copper according to claim 3, characterized in that: The auxiliary dispersant is an EO-PO block polyether copolymer dispersant.
5. The nanometer aqueous suspension of quinoline copper according to claim 4, characterized in that: The wetting agent is a fatty alcohol polyoxyethylene ether or diisopropylnaphthalene sulfonate wetting agent.
6. The nanometer aqueous suspension of quinoline copper according to claim 5, characterized in that: The preservative is a benzisothiazolinone preservative, which should be prepared into a 2% to 3% aqueous solution when used.
7. The nanometer aqueous suspension of quinoline copper according to claim 6, characterized in that: The defoaming agent is one of modified polyether, acetylene glycol and organosilicon defoaming agent, and the antifreeze agent is one of propylene glycol, ethylene glycol and urea.
8. The nanometer aqueous suspension of quinoline copper according to claim 7, characterized in that: The thickener is one or more of xanthan gum, magnesium aluminum silicate, cellulose and hydroxyethyl cellulose. The xanthan gum needs to be prepared into an aqueous solution when used, and the xanthan gum needs to be prepared into a 1-2% aqueous solution.
9. A method for preparing a nanometer aqueous suspension of quinoline copper according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1: Mix and stir evenly 20-45% of quinoline copper, 5-20% of dispersant, 1-5% of dispersant aid, 1-5% of wetting agent, more than 90% of thickener (0.2-3%), 1-10% of antifreeze, 40-60% of defoamer (0.1-1%), and 60-80% of water; S2: adding the mixture in S1 into a nano-scale sand mill with zirconium oxide beads for sand grinding; S3: After the particle size of S2 is sand-milled to 200-900 nm, add the remaining 40-60% defoamer, the remaining thickener, the preservative and the remaining water, stir and disperse evenly to obtain the nano pesticide suspension.
10. The nanometer aqueous suspension of quinoline copper according to claim 9, characterized in that: In the step of mixing and stirring, 0.9-2% of magnesium aluminum silicate thickener is added. In the step of mixing and stirring, the particle size of the zirconium oxide beads is 0.1- 0.6mm, in said S3, after the particle size reaches 200-900nm, add 0.1-0.5% of xanthan gum aqueous solution thickener.